2020
DOI: 10.1177/1744806920963807
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced T-type calcium channel 3.2 activity in sensory neurons contributes to neuropathic-like pain of monosodium iodoacetate-induced knee osteoarthritis

Abstract: The monosodium iodoacetate knee osteoarthritis model has been widely used for the evaluation of osteoarthritis pain, but the pathogenesis of associated chronic pain is not fully understood. The T-type calcium channel 3.2 (CaV3.2) is abundantly expressed in the primary sensory neurons, in which it regulates neuronal excitability at both the somata and peripheral terminals and facilitates spontaneous neurotransmitter release at the spinal terminals. In this study, we investigated the involvement of primary senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 75 publications
1
29
0
Order By: Relevance
“…Since the spinal cord DH receives innervation from DRG-PSNs, we next evaluated by IHC whether CFA pain was associated with altered Piezo2 expression in the DH. For quantitative comparison, we normalized Piezo2-IR intensity on the side ipsilateral to CFA by using the contralateral side in the same section as the control [14, 57], assuring that all IHC preparation and image capture parameters are identical in the same cross-section. To validate the use of general IR intensity of the DH as a quantitative indicator of protein expression in sensory neurons, we compared IB4 and CGRP staining in the DH from SNI rats, in which quantitatively decreased IB4 and CGRP immunoreactive intensity in sensory neurons ipsilateral to the SNI injury is expected [37, 80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the spinal cord DH receives innervation from DRG-PSNs, we next evaluated by IHC whether CFA pain was associated with altered Piezo2 expression in the DH. For quantitative comparison, we normalized Piezo2-IR intensity on the side ipsilateral to CFA by using the contralateral side in the same section as the control [14, 57], assuring that all IHC preparation and image capture parameters are identical in the same cross-section. To validate the use of general IR intensity of the DH as a quantitative indicator of protein expression in sensory neurons, we compared IB4 and CGRP staining in the DH from SNI rats, in which quantitatively decreased IB4 and CGRP immunoreactive intensity in sensory neurons ipsilateral to the SNI injury is expected [37, 80].…”
Section: Resultsmentioning
confidence: 99%
“…Lumbar spinal cord sections from control rats and from rats subjected to CFA inflammatory pain, as well as archival spinal cord sections from neuropathic pain models of SNL, SNI, and TNI (4wk post injury), and MIA-OA pain (5wk after MIA knee injection), as previously reported [37, 57-59, 80, 81], were used to evaluate whether pain is associated with alteration of Piezo2 expression in the DH. For quantification of DH piezo2 immunostaining, the Image J v.1.46 was used to quantify changes in immunolabeled fluorescent intensities as described previously [14, 57], with some minor modifications. In brief, the sections with symmetrical width of DH throughout the mediolateral axis were used for measurement, and the upper and lower threshold optical intensities were adjusted to encompass and match the immunoreactivity (IR) that appears in red.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that the expression of Ca V 3.2 channels is increased in spinal dorsal horn or DRG neurons in models of chronic nerve injury ( 46 51 ), inflammatory pain models ( 52 56 ), acute pain model ( 57 ) as well as in chemically induced neuropathies ( 58 ) including diabetic neuropathy ( 40 , 59 ).…”
Section: The Mechanisms Of the Development Of Peripheral Diabetic Neu...mentioning
confidence: 99%
“…Expression in cell membranes of T-type CaV3.2 calcium channels and their activation in the dorsal root ganglion (DRG) damaged neurons in mice with neuropathic pain increase after spared nerve injury. Antisense inhibition may decrease mechanical allodynia 14 days after spared nerve injury, suggesting that CaV3.2 T-type calcium channels play a role in damaged DRG-mediated neurons (66). The CaV3.2 membranes of medium-sized DRG neurons play a considerable function in neuropathic pain (67).…”
Section: Calcium Channels and Neuropathic Painmentioning
confidence: 99%